Standing flank laparotomy for colic: 37 cases. (6th October 2021) - Lopes, Marco A. F.; Hardy, Joanne; Farnsworth, Kelly; Labens, Raphael; Lam, W. Y. Eunice; Noschka, Erik; Afonso, Tiago; Cruz Villagrán, Claudia; Santos, Luiz C. P.; Saulez, Montague; Kelmer, Gal
Abstract: Background: Standing flank laparotomy can be an alternative to ventral midline laparotomy in horses with colic. Standing flank laparotomy avoids general anaesthesia, provides excellent access to some regions of the abdominopelvic cavity and costs less than ventral midline laparotomy. Objective: To report a series of cases of peritoneal and intestinal diseases other than SC diseases managed with standing flank laparotomy. Study design: Retrospective case series. Methods: Records from equids with colic subjected to standing flank laparotomy at five hospitals (2003‐2020) were reviewed. Descriptive data analysis was performed. Results: Thirty horses (sixteen survived to discharge), six ponies (four survived) and one donkey (euthanised) were subjected to standing flank laparotomy via the left flank (n = 31), right flank (n = 2) or both flanks (n = 4). The primary disease affected the peritoneum (0/5 survived), SI (5/9 survived) and caecum and/or LC (15/23 survived). Enterotomy was performed in four animals (all survived). Partial typhlectomy was performed in one horse (euthanised). Resection‐anastomosis of the SI or LC was performed in three animals (one survived). Three animals had intraoperative complications that negatively affected the outcome: Two ponies had intolerance to abdominopelvic exploration; one mare had spontaneous exteriorisation of a long segment of the SI leading to a large tear in the mesentery. In seven cases, severe/extensive lesions found during standing flank laparotomy warranted immediate euthanasia. The survival rate was 54%. All owners were satisfied with the decision to perform standing flank laparotomy. Main limitations: The retrospective design, lack of a control group, small number of cases and lack of standardised protocols between hospitals. Conclusions: Although ventral midline laparotomy is the standard of care for horses with colic, standing flank laparotomy is a viable approach for some types of colic. Systemic administration of analgesics may not produce sufficient peritoneal analgesia, which can lead to intolerance to abdominopelvic exploration during standing flank laparotomy in horses with colic and may negatively affect the outcome.